Upaya peningkatan hasil belajar matematika menggunakan cooperative learning - Agus Suprianto; Yari Dwikurnaningsih (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The purpose of this research is to the improve of cognitive learning results of fourth grade mathematics which is the achievement school but have learning result that is still felt less of satisfactory. The type of research which used is Classroom Action Research and implemented as much as 2 cycles. The research learning model used in this research is cooperative learning. Instruments used in this study are formative test sheets, observation sheets, interviews, and documentation. In the implementation of the first cycle, there is a change in the improvement of cognitive learning outcomes after the actions in cycle II. So it can be concluded that learning by cooperative learning model can improve cognitive learning results of mathematics.